2015
DOI: 10.1523/jneurosci.1873-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Reach Trajectories Characterize Tactile Localization for Sensorimotor Decision Making

Abstract: Spatial target information for movement planning appears to be coded in a gaze-centered reference frame. In touch, however, location is initially coded with reference to the skin. Therefore, the tactile spatial location must be derived by integrating skin location and posture. It has been suggested that this recoding is impaired when the limb is placed in the opposite hemispace, for example, by limb crossing. Here, human participants reached toward visual and tactile targets located at uncrossed and crossed fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
4
17
0
Order By: Relevance
“…This finding replicates our observation in a free-viewing task of natural scenes (Ossandón et al, 2015). While a purely external effect of touch on saccades is in agreement with previous studies (Groh and Sparks, 1996;Blanke and Grüsser, 2001;Overvliet et al, 2011;Buchholz et al, 2012), both saccades and reaches towards tactile locations can exhibit trajectories that initially deviate towards the anatomical side of the tactile event (Groh and Sparks, 1996;Overvliet et al, 2011;Brandes and Heed, 2015). Note that, in those tasks, the tactile stimulus location was the movement goal.…”
Section: Behavioral Correlates Of Tactile Stimulationsupporting
confidence: 92%
See 3 more Smart Citations
“…This finding replicates our observation in a free-viewing task of natural scenes (Ossandón et al, 2015). While a purely external effect of touch on saccades is in agreement with previous studies (Groh and Sparks, 1996;Blanke and Grüsser, 2001;Overvliet et al, 2011;Buchholz et al, 2012), both saccades and reaches towards tactile locations can exhibit trajectories that initially deviate towards the anatomical side of the tactile event (Groh and Sparks, 1996;Overvliet et al, 2011;Brandes and Heed, 2015). Note that, in those tasks, the tactile stimulus location was the movement goal.…”
Section: Behavioral Correlates Of Tactile Stimulationsupporting
confidence: 92%
“…However, one must bear in mind that our time estimates are averages across many trials, and that the stimulation only affected some saccades at 100 ms, becoming more consistent only at later time points. In a previous study, we compared when participants initiated a turn of a straight hand reach towards a visual or a tactile stimulus, presented in-flight (Brandes and Heed, 2015). Tactually evoked turns were only 20 ms slower after tactile stimulation to uncrossed limbs than to visual stimuli at identical locations, thus suggesting a very short estimate for the computation of an externalspatial location of touch.…”
Section: Behavioral Correlates Of Tactile Stimulationmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been suggested that a full random effects structure should be 321 used for significance testing in (G)LMM (Barr, Levy, Scheepers, & Tily, 2013). However, it has been shown 322 that conclusions about fixed effect predictors do not diverge between models with maximal and models 323 with parsimonious random effects structure(Bates, Kliegl, Vasishth, & Baayen, 2015), and it is common 324 practice to include the maximum possible number of random factors when a full structure does not 325 result in model convergence (e.g.,Bolker et al, 2009;Brandes & Heed, 2015). In the present study, 326 models reliably converged when we included random intercepts and slopes per participant for each main 327 effect, but not for interactions.…”
mentioning
confidence: 54%